Perceptions regarding medication administration errors among Medical And Surgical Nurses In Hospital USM - Safar, Nur Amanina Sofea (Universiti Sains Malaysia, 2016)
Medication administration errors (MAEs) has been a major global issues as it caused serious health threatening which increase mortality rates, length of hospital stay, and related costs for the patients as well as affecting the nursing professionalism. This study was aimed to identify the factors that contributed to MAEs and determine the association between selected socio-demographic and MAEs in medical and surgical wards nurses in Hospital USM. The research design used for this study was quantitative cross-sectional survey design by using an adapted self-administered questionnaire. Ninety-eight nurses were recruited through simple random sampling from medical and surgical based wards. This research was approved by ethical approval department from Research Ethics Community (Human), USM. The findings showed that the factor that causing MAEs in medical and surgical based wards were medication packaging (59.2% agreed, n = 58) and physician communication (52.4% agreed, n = 51). The items that was common to cause errors based on the two factors above were medication look alike (M= 3.79, SD = 1.44) and physician medication orders are not clear (M=3.85, SD= 1.58), respectively. There were no significant difference between medical and surgical wards in terms of factors causing MAEs with p >0.05 for all the identified factors. Socio demographic played a role in modifying the frequency of occurrence of MAEs in both wards. With p < 0.05 in relationship between working experience and factors MAEs, this showed that increase in years of working experience will reduce the frequency of MAEs to occur. However, gender and age did not have any affect towards factors causing MAEs. The study recommended that the continuation of nursing education and practice of guidelines on medication administration as well as mentorship program about medication administrations should be applied to ensure patient safety and the credibility of nursing.